Candida-associated denture stomatitis: clinical, epidemiological, and microbiological features - Qiu, Jiuyan; Roza, Milena P.; Colli, Karolyne G.; Dalben, Yago R.; Maifrede, Simone B.; Valiatti, Tiago B.; Novo, Vinicius M.; Cayô, Rodrigo; Grão-Velloso, Tânia Regina; Gonçalves, Sarah S. (Brazilian journal of microbiology, 2023)
Objective The identification of Candida spp. in denture stomatitis, the clinical manifestations, and the antifungal susceptibility profile lead to a correct and individualized therapeutic management of the patients. This study is aimed at investigating the clinical manifestations and epidemiological and microbiological characteristics of Candida -associated denture stomatitis. Design The samples were obtained by swabbing the oral mucosa of the subjects and then seeded onto Sabouraud Dextrose Agar and onto CHROMagar® Candida plates. The identification at the species level was confirmed by Matrix Assisted Laser Desorption Time of Flight Mass Spectrometry. Clinical classification was performed according to the criteria proposed by Newton (1962): (i) pinpoint hyperemia, (ii) diffuse hyperemia, and (iii) granular hyperemia. For carrying out the antifungal susceptibility testing, we adopted the CLSI M27-S4 protocol. Results C. albicans was the most prevalent species in our study. Regarding non- albicans Candida species, C. glabrata was the most common species isolated from the oral mucosa ( n = 4, 14.8%), while in the prosthesis, it was C. tropicalis ( n = 4, 14.8%). The most prevalent clinical manifestation was pinpoint hyperemia and diffuse hyperemia. Candida albicans , C. glabrata , and C. parapsilosis were susceptible to all the tested antifungals. Concerning fluconazole and micafungin, only two strains showed dose-dependent sensitivity (minimum inhibitory concentration (MIC), 1 μg/mL) and intermediate sensitivity (MIC, 0.25 μg/mL). One C. tropicalis strain was resistant to voriconazole (MIC, 8 μg/mL). Conclusions C. albicans was the most common species found in oral mucosa and prosthesis. The tested antifungal drugs showed great activity against most isolates. The most prevalent clinical manifestations were Newton’s type I and type II.